Dragon Age. Dark fortress - DeFilippis, Nunzio; Weir, Christina (Dragon Age, 2021)
"Fenris and the Inquisition race to keep the Venatori from unleashing a power that will reshape Thedas in this canonical continuation of BioWare's dark fantasy RPG! Deep within the Tevinter Imperium, with the invading Qunari armies hot on their heals, a fearless team prepares to assault a fortress said to be unbreakable in a bid to prevent the unthinkable from being unleashed. Among them is the deadly Fenris, the brave Ser Aaron Hawthorne and his squire/thief Vaea, the troubled mage Francesca Invidus, and the mage-killing team of Tessa Forsythia and Marius. Will they be fast enough to outrun their own pasts and stop what's coming?" -- Amazon.com.